PREFERENCES FOR ONLINE Vs. TRADITIONAL TRAVEL RESERVATION - MALIK ELHAJ (Centre For Tourism Planning and Development, 2011)
Quantitative survey data were collected from U.S. citizens to determine the extent to which trip destination (domestic or international) and trip purpose (business, leisure, or personal) affected consumers' preferences for traditional versus online reservation systems. The results indicated that the participants preferred travel agent phone calls for all types of international flights, but online airline websites and online travel agent websites for domestic flights. Online airline websites were preferred for business trips. Stakeholders in online and traditional travel agents can use the results from this study to remain competitive as the travel industry evolves.